Swiftlet House Cooling System Powered by Solar Panel - BARRY, GIDEON; Bakar, Lilywati (Progress in Engineering Application and Technology, 2021)
In every Season of the year Malaysia will encounter hot season which will cause damage to some ecosystem and habitat. To overcome this type of problem with the help of Arduino, it can manage the system and ease some people by saving their time to do all the work manually. In this project, Swiftlet House Cooling System Powered by Solar Panel will able to achieve and solve problem which focusing more in the habitat of swiftlet. This system will be using the technique of cooling the building itself so that it able to create the perfect and suitable environment for the swiftlet to creating their nest. The temperature sensor that will be installed inside of the building will record and send a signal to Arduino which is the brain of the system about the condition inside of the building. The Arduino will take some action if needed by sending signal to other equipment to handle this situation automatically